2020
DOI: 10.1101/2020.09.10.285049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A simple permutation-based test of intermodal correspondence

Abstract: Many key findings in neuroimaging studies involve similarities between brain maps. While several statistical procedures have been proposed to test correspondence between maps, there remains no consensus on the correct framing of a null hypothesis or a suitable testing approach. We propose a simple yet powerful permutation-based testing procedure for assessing similarities between two modalities using subject-level data. Our proposed method is similar to traditional permutation procedures in that it involves ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…It is also informative to consider a setting in which we do not expect to see strong intermodal associations. Thus, we consider correspondence tests between cortical thickness and n-back task activation, as previous work has not suggested we would expect either global or local correspondence between these modalities [9]. Cortical thickness is quantified as the minimum distance between pial and white matter surfaces.…”
Section: H 0 In Contextmentioning
confidence: 99%
See 3 more Smart Citations
“…It is also informative to consider a setting in which we do not expect to see strong intermodal associations. Thus, we consider correspondence tests between cortical thickness and n-back task activation, as previous work has not suggested we would expect either global or local correspondence between these modalities [9]. Cortical thickness is quantified as the minimum distance between pial and white matter surfaces.…”
Section: H 0 In Contextmentioning
confidence: 99%
“…Methodological developments in this area have included statistical estimation of individual-level maps measuring intermodal coupling [1,2,3,4,5] and hypothesis tests for establishing statistical significance of intermodal associations [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This procedure is repeated until a desired number (here, 10,000) of permutations have been performed, and the final permutation P value reflects the number of null permutations for which the resulting Spearman correlation is greater than the observed correlation divided by the total number of permutations. Although recent work has identified that this approach relies upon often unrealistic statistical assumptions (Weinstein et al, 2020), we note that no alternative method is compatible with our effect maps which are undefined at the individual subject level.…”
Section: Spatial Permutation Testsmentioning
confidence: 67%